2022
DOI: 10.1002/solr.202200798
|View full text |Cite
|
Sign up to set email alerts
|

Laser Processing of KBr‐Modified SnO2 for Efficient Rigid and Flexible Ambient‐Processed Perovskite Solar Cells

Abstract: A combination of KBr modification and laser processing is utilized to prepare SnO2 films for rigid and flexible perovskite solar cells (PSCs). The KBr modification effectively passivates the defects at the interface between SnO2 and perovskite as well as grain boundaries of the perovskite film. A power conversion efficiency (PCE) of 20.14% is achieved with the KBr‐modified SnO2 for the rigid PSCs fabricated under a relative humidity of around 65–75%, compared to the pristine SnO2 films with a PCE of 18.66%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…We use ethyl acetate as a green antisolvent to facilitate crystallisation of the perovskite layers in a one-step deposition process, as reported in our previous works. [32][33][34] Fig. 1a shows a schematic structure of the PSCs: ITO-glass/ c-TiO 2 /m-TiO 2 /perovskite/Spiro-OMeTAD/Au.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use ethyl acetate as a green antisolvent to facilitate crystallisation of the perovskite layers in a one-step deposition process, as reported in our previous works. [32][33][34] Fig. 1a shows a schematic structure of the PSCs: ITO-glass/ c-TiO 2 /m-TiO 2 /perovskite/Spiro-OMeTAD/Au.…”
Section: Resultsmentioning
confidence: 99%
“…The c-TiO 2 and m-TiO 2 films were prepared and spin-coated according to the procedures detailed in our previous studies. 32,33 The films were then annealed in a muffle furnace with a temperature of 500 1C for 30 min. For Li-doped m-TiO 2 , deionised water was used to dissolve various amounts of Li 2 CO 3 to obtain the Li-salt solution with varied concentrations (0.5, 1.0, 1.5 mg mL À1 ).…”
Section: Preparation Of LImentioning
confidence: 99%
“…[29] The diffused K þ ions could passivate defects of the PVK absorber layer. [29,30] The interaction mechanism of SPS modification is shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…Above investigation found that STRS‐SnO 2 can absorb more strain energy than SnO 2 itself and thus is expected to enable a highly efficient and mechanically stable F‐PSC. [ 72,73 ]…”
Section: Resultsmentioning
confidence: 99%
“…Above investigation found that STRS-SnO 2 can absorb more strain energy than SnO 2 itself and thus is expected to enable a highly efficient and mechanically stable F-PSC. [72,73] F-PSCs with an architecture of PET/ITO/SnO 2 /perovskite/Spiro-OMeTAD/Ag were fabricated to investigate their photovoltaic performance and mechanical flexibility, as shown in Figure 9a. A champion F-PSC made with STRS additive in ETL (active area 0.09 cm 2 ) remarkably achieves a PCE of 20.79% with V oc of 1.168 V, J sc of 22.289 mA cm −2, and FF of 0.798 (Figure 9b).…”
Section: Strs Application In Flexible Pscsmentioning
confidence: 99%